Non-specialized Lexical Units Functioning in the Publicistic Texts on Economic Topics (Linguostylistic Studies, 2019)
The article analyzes the non-specialized lexical units, most commonly used in the economic discourse, which denote actions, processes, and states related to money.  The study identifies functional-stylistic features of these lexical items in the texts of modern mass media and traces an enlargement of the economic lexical group by means of the lexemes from other thematic groups. The article describes the stylistic role of the non-specialized lexical items in the topics on economics with an emphasis on their negative assessment in the language of modern mass media genres.The purpose of the article is to analyze non-specialized economic vocabulary in the Ukrainian mass media against the background of social dynamics, to substantiate a functional-stylistic diffuseness of vocabulary as one of the defining tendencies in the development of the Ukrainian language.The material of the research is a body of lexical items, selected from the language of national and regional mass media. The descriptive research method and observation method were used as basic in this scientific research. At different stages of the research, the method of functional analysis was used to determine the stylistic load of lexical items and the comparative method – to analyze individual lexical positions, which are used in different styles of Ukrainian literary language.The article concludes that the use of lexical items with a figurative meaning for denoting economic actions, processes, and states has increased in the language of modern Ukrainian mass media. The updating of the economic vocabulary is caused by the influence of various extralinguistic factors. For the most part, the meaning of lexical units is related to wasting or total loss of money. Such linguistic items in economic topics are classified as non-specialized lexical items, that is, belonging to different lexical-semantic groups and used in their figurative meaning. Non-specialized lexical items are mostly related to the verbs of physical action, usually stylistically marked, correlated with the informal style, and have a distinct pejorative coloring. With the help of the negative-assessed lexical items, the authors create appropriate vivid characteristics of those, who enrich at the expense of others, wasting money and committing fraud. The analyzed lexical items reflect the negative processes in the economic life of society and also confirm the progression of the tendency of non-specialized lexical items functioning in the economic topics.The prospect of further research concerns the study of lexical units of other lexical and semantic groups, which will expand the study of the non-specialized economic vocabulary of the Ukrainian media against the background of social dynamics.
Keywords: lexical items of economic field; non-specialized lexical items; lexical meaning; mass media language; stylistic role